The Spread of Hoaxes on Social Media: A Communication Analysis and Legal Review of the ITE Law - Olih Solihin; Sahat Maruli Tua Situmeang; Safutra Rantona rantona; Yuni Mogot rantona (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The rapid evolution of digital technology has transformed social media into the primary platform for information dissemination. While it offers speed and accessibility, social media also enables the uncontrolled spread of misinformation and hoaxes. This study aims to describe the pattern of hoax dissemination on social media from a digital communication perspective and to analyze how Indonesian Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law) responds to this phenomenon from a legal standpoint. Using a descriptive qualitative method based on literature review, this study combines communication theories—particularly framing and agenda setting—with normative legal analysis. Hoaxes are often framed emotionally and sensationally to attract public attention and manipulate perception. Through agenda setting mechanisms, such content dominates digital discourse, reinforcing its perceived importance regardless of truth. The findings suggest that the spread of hoaxes is driven not only by content but also by algorithmic amplification and public vulnerability due to low digital literacy. While the ITE Law provides a legal framework to address online misinformation, its enforcement faces challenges such as ambiguous legal language and difficulties in proving intent. Therefore, an interdisciplinary approach combining communication strategy and legal reform is needed to effectively combat the hoax epidemic. This study contributes to both academic discourse and policy recommendations aimed at building a more informed and resilient digital society.